Chemical composition of Yamato (Y) 000593 and Yamato 000749: Neutron-induced prompt gamma-ray analysis study - Oura, Yasuji; Shirai, Naoki; Ebihara, Mitsuru (National Institute of Polar Research, 2003)
P(論文) Neutron-induced prompt gamma-ray analysis (PGA) was applied to Antarctic nakhlites, Yamato (Y) 000593 and Y000749 together with Nakhla for the non-destructive determination of most major and minor elements (plus some trace elements). In addition to analyses of lump samples of these three meteorite, powder samples representing six different portions within Y000593 also were analyzed for discussing the chemical heterogeneity. As a result, it was confirmed that most major elements are homogeneously distributed among Y000593 within an error of ±10%. Chemical compositions of Y000593 and Y000749 are essentially identical within error limits, supporting the suggestion that these meteorites are paired. Compositional similarity is also confirmed between Nakhla and Y000593 (and Y000749), verifying that Y000593 (and Y000749) belong to nakhlites. Based on our PGA data coupled with literature data for Martian meteorites, we propose a diagram used for classifying achondrites and further for grouping into individual groups of Martian meteorites. Although there are some scatterings in B and Cl data, we would propose their abundances in nakhlites to be 3.33 ppm and 80 ppm, respectively. Our H data are systematically higher than their literature data. Although further refinements in our analytical procedure of PGA are required for getting more reliable and accurate values of H in Martian meteorites, it is suspected that some literature values of H contents in Martian meteorites are a little too small. departmental bulletin paper